Spatial-temporal pattern analysis of landscape ecological risk assessment based on land use/land cover change in Baishuijiang National nature reserve in Gansu Province, China. (May 2021) - Wang, Hong; Liu, Xingming; Zhao, Chuanyan; Chang, Yapeng; Liu, Youyan; Zang, Fei
Graphical abstract: Highlights: The LULC change features were the increase of forest and decrease of cultivated land. Landscape ecological risk increased during 1986–2008 and declined during 2008–2015. Human management intensities deeply affected landscape ecological risk in reserves. Abstract: It is necessary to improve the ecological environment and keep ecological balance of nature reserves that have particularly important function on precious and endangered wildlife species conservation. Human activities give rise to the remarkable changes in land use/land cover (LULC) and further have an effect on the landscape and eco-environment in nature reserves. This study evaluated the landscape ecological risk based on LULC changes in Baishuijiang National Nature Reserve according to different management zones from 1986 to 2015. Results showed that the significant change characteristics of LULC were the increase of forest and the decrease of cultivated land from 1986 to 2015. The major LULC changes took place in the experimental zone, and there was 85.61 km 2 cultivated land transferred to the forest. Generally, the ecological risk level was low, and the area percentages of the lowest and lower risk regions to the total area were all higher than 97% from 1986 to 2015. Moreover, the values of ecological risk were discrepant in different time, the order of that being 1986 < 2015 < 1995 < 2008. Combining the components of different ecological risk levels in every management zone, the ecological risk from low to high was the core zone, buffer zone, and experimental zone. The ecological risk tended to be aggregated in space during 1986–2008, and it was enhanced slightly from 2008 to 2015. This study focuses on Baishuijiang National Nature Reserve to provide assessment for environmental protection and ecological management in hope that the method can be applied to other national nature reserves in China.